Effect of shear strain compatibility and incompatibility approaches in the design of high modulus columns against liquefaction: A case study in Christchurch, New Zealand - Demir, Selcuk; Ozener, Pelin (SPRINGER, 2022)
Nowadays, investigating the effectiveness of high modulus columns in liquefaction mitigation is one of the important tasks in earthquake geotechnical engineering. Although there is limited data from the field and laboratory to verify the performance of high modulus columns (HMCs), available case histories, physical model tests, and reliable numerical methods provide important information in order to analyze the role of HMCs in liquefaction mitigation. In this paper, the seismic performance of a liquefied site improved with rammed aggregate piers (RAPs) is investigated through the results of a full-scale field test. Results of cone penetration test (CPT) and cross-hole shear wave velocity (V-s) test before and after RAP treatment at the test site are assessed to achieve properties of the natural (unimproved) soil, RAP, and the surrounding (improved) soil. The effectiveness of RAPs in liquefaction mitigation is evaluated in terms of pre-and post-improvement factor of safeties against liquefaction, liquefaction-induced deformations, and ground failure indices, which are calculated using shear strain compatibility and incompatibility approaches. The research results showed that RAPs exhibit a satisfying performance when computations are made considering shear strain compatibility in the computation of seismic shear stress reduction factor. On the contrary, the effectiveness of RAPs during the shear strain incompatibility approach is significantly smaller than the ones computed from the current design method based on shear strain compatibility approach. The findings of this study provide a basis for the performance-based ground improvement design through HMCs to mitigate soil liquefaction and also extend knowledge about HMC-improved seismic soil response by presenting the results of liquefaction vulnerability parameters before and after soil improvement of a field test study.
Keywords: High modulus columns; Liquefaction mitigation; Rammed aggregate piers; Soil improvement; Shear strain compatibility; CENTRAL BUSINESS DISTRICT; PERFORMANCE; MITIGATION; BRIDGES; DAMAGE; Engineering; Geology